Surgery for bone sarcomas of the lower extremity. Issue 6 (November 2016) - Holt, Ginger E.; Wilson, Robert J.
Abstract : Surgery for lower extremity bone sarcomas encompasses a wide array of surgical options beyond the classic treatment of amputation. Limb salvage surgery (LSS) in the form of arthroplasty, arthrodesis, or allograft reconstruction is now possible for most patients. Patient function, in addition to survival, has been increasingly emphasized as the 5-year survival is now typically over 60%. Recent research looking at the activity levels of patients after endoprosthetic reconstruction is reviewed. Advances in surgical navigation, expandable endoprostheses, and in treating infected allografts and endoprostheses are summarized. Long-term functional outcomes and neurologic plasticity in patients with rotationplasties are examined as well. Surgery for bone sarcomas remains a high-risk, high-reward endeavor that continues to improve through innovation.